2019
DOI: 10.1177/0267659119842060
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus conventional extracorporeal circulation circuits in patients undergoing coronary artery bypass surgery: a propensity-matched analysis

Abstract: Objectives: Minimally invasive extracorporeal circulation circuits provide several advantages compared to conventional extracorporeal circulation circuits. We compared the results of a minimally invasive extracorporeal circulation system with those of conventional extracorporeal circulation system, in patients undergoing isolated coronary artery bypass grafting. Methods: We identified 753 consecutive patients who underwent coronary artery bypass grafting at our centre between October 2014 and September 2016. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To maximize perioperative safety, MICS patients must undergo preoperative evaluation to exclude individuals with (I) valvular disease, ventricular aneurysm, or a requirement for extracorporeal circulation surgery, (II) patients with a left ventricular ejection fraction (LVEF) ≤50%, (III) patients with a closed chest due to thoracic deformities or severe pleural adhesions, and (IV) patients with severe lung disease and difficulties tolerating single-lung ventilation (11)(12)(13)(14), (V) patient had severe calcification of the ascending aorta, (VI) patient's requirements. Patients in the present study in the MICS group were more likely to be male, and were less likely to have comorbid pulmonary disease, prior CVA, prior MI, and mild CAD.…”
Section: Discussionmentioning
confidence: 99%
“…To maximize perioperative safety, MICS patients must undergo preoperative evaluation to exclude individuals with (I) valvular disease, ventricular aneurysm, or a requirement for extracorporeal circulation surgery, (II) patients with a left ventricular ejection fraction (LVEF) ≤50%, (III) patients with a closed chest due to thoracic deformities or severe pleural adhesions, and (IV) patients with severe lung disease and difficulties tolerating single-lung ventilation (11)(12)(13)(14), (V) patient had severe calcification of the ascending aorta, (VI) patient's requirements. Patients in the present study in the MICS group were more likely to be male, and were less likely to have comorbid pulmonary disease, prior CVA, prior MI, and mild CAD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all 40 patients underwent anterior descending coronary artery bypass graft. Beating-heart coronary artery bypass surgery requires single-lung ventilation [Saha 2019], which is prone to decrease blood oxygen saturation during operation, and its decrease is closely related to the occurrence of POCD [Lopez 2017]. The incidence of POCD in the first week after cardiac surgery has been reported to be as high as 30-60%, which may prolong the length of hospital stay, reduce the quality of life, increase postoperative mortality, and cause a serious burden on individuals and society [Mashour 2015].…”
Section: Discussionmentioning
confidence: 99%
“…17,29,47,51 Multiple recent studies have consistently confirmed these findings. 18,[42][43][44][45][46] The significant hematologic effects of MiECC in terms of blood conservation have been integrated by EACTS/EACTA Task Force in an intraoperative strategy for maintenance of hemostasis and blood conservation management in adult cardiac surgery (Class of Recommendation IIA, Level of Evidence B). 77 More recently, STS/Society of Cardiovascular Anesthesiologists (SCA)/American Society of ExtraCorporeal Technology (AmSECT)/Society for the Advancement of Blood Management (SABM) update to the clinical practice guidelines on patient blood management (PBM) also advocates MiECC as part of a combined blood conservation approach.…”
Section: Anesthesia For Surgery On Mieccmentioning
confidence: 99%